Diagnostic value of N-methyl-D-aspartate receptor antibodies in women with new-onset epilepsy. - Niehusmann, P; Dalmau, J; Rudlowski, C; Vincent, A; Elger, C; Rossi, J; Bien, C (2009)
BACKGROUND: In women younger than 45 years, a new form of encephalitis associated with ovarian teratoma and presenting with seizures and psychiatric symptoms has been described. Most patients have antibodies to NR1/NR2 heteromers of the N-methyl-D-aspartate receptor (NMDAR). OBJECTIVE: To assess the frequency and significance of antibodies to NMDAR in otherwise unexplained new-onset epilepsies in young women. DESIGN: Prospective cohort study. SETTING: University department of epileptology. PATIENTS: From January 1, 2005, to June 30, 2007, we identified 19 female patients aged 15 to 45 years with unexplained new-onset epilepsy. In addition, we studied 61 cerebrospinal fluid-serum sample pairs from patients with other cryptogenic epilepsies and 11 cerebrospinal fluid-serum sample pairs from surgically treated patients with epilepsy with no evident encephalitic abnormalities. MAIN OUTCOME MEASURES: Antibodies to NMDAR and characteristics of affected patients. RESULTS: Five of the 19 patients had antibodies against NMDAR. These patients had diffuse cerebral dysfunction and seizure origins. Psychiatric symptoms and pleocytosis were significantly associated with this group of patients. The disease course was episodic, in part relapsing-remitting, with full recoveries either spontaneously or after corticosteroid or intravenous immunoglobulin treatments. Only 1 patient had a neoplasm (multiple neuroendocrine tumors that included the ovaries) identified to date. In the control series, one 22-year-old man with a cryptogenic, severely encephalopathic seizure disorder was NMDAR antibody positive, and he also recovered fully. CONCLUSIONS: Anti-NMDAR encephalitis accounts for a relevant proportion of otherwise unexplained new-onset epilepsies. Patients harboring NMDAR antibodies usually have prominent psychiatric symptoms and pleocytosis, and they may develop hypoventilation. Anti-NMDAR encephalitis is not always paraneoplastic.